Intergenerational mentoring, eudaimonic well-being and gene regulation in older adults: A pilot study. (January 2020) - Seeman, Teresa; Merkin, Sharon Stein; Goldwater, Deena; Cole, Steven W.
Highlights: Serving as a school mentor was correlated with a reduction in the conserved transcriptional response to adversity (CTRA). Decreases in CTRA gene expression correlated with increases in eudaimonic well-being (net of hedonic well-being change). The GenX school mentoring program may potentially have favorable effects on leukocyte gene regulation. Abstract: To clarify the biological mechanisms underlying the relationship between pro-social behavior and health, this pilot study examined the impact of a 9-month intergenerational helping intervention on conserved transcriptional response to adversity (CTRA) gene expression profiles, which are characterized by up-regulation of genes involved in inflammation and down-regulation of genes involved in antiviral defenses. The Generation Xchange program trains and places older (age 50+) volunteers in K-3 rd grade classrooms to aid students' academic development (reading and math) and address behavioral issues (e.g., inability to focus during class, behaviors that disrupt class). Volunteers were predominately women (89%) and African American (94%) from the neighborhoods around the schools. Repeated measures planned contrast analysis of 53 CTRA indicator transcripts in 50 blood samples collected from 18 individuals on 2–3 occasions revealed a significant reduction in CTRA gene expression from baseline to the average of 3- and 9-month follow-up. The magnitude of individual decrease in CTRA gene expression correlated with the magnitude of individual increase in eudaimonic well-being over time (net of changes in hedonic well-being). In addition to clarifying biological pathways through which pro-social behavior might impact health, these pilot data suggest that the GenX program may have favorable effects on immune cell gene regulation.